Building organizational resilience of public extension system during pandemic in Enugu State Nigeria - Anugwa, Ifeoma Quinette; Babu, Suresh Chandra; Agwu, Ekwe Agwu; Madukwe, Michael (African Journals Online, 2024)
The study identified potential changes in the public extension system that could contribute to food system transformation during the pandemic. Document reviews, surveys, focus group discussions, and key informant interviews were used to achieve the study objectives. During the COVID-19 pandemic, most (96.0%) rural households had no extension contact resulting in challenges within the food production system. The annual quantity of yam produced by the respondents declined from an average of 5,700kg pre-pandemic era to 5,100kg during the pandemic. As a result of the pandemic, the already weak extension system was exposed to greater vulnerability due to weak capacity, poor competence, and technical know-how needed to drive the food production system transformation. Policy interventions are recommended to ensure that extension services are digitalized, human capacities are improved and adequate funding is available.